Accessibility for persons with disabilities and the inclusive future of libraries - Wentz, Brian; Jaeger, Paul T., 1974-; Bertot, John Carlo (Bingley, U.K. : Emerald, 2015)
All libraries have patrons and staff members with disabilities, making equitable service a priority for these organizations as they provide diverse services to their entire communities. Although rapid technological changes in recent years have offered challenges to libraries, these same technologies provide opportunities to embrace the concept of accessible library services and create innovative new services for patrons with disabilities. Accessibility for persons with disabilities and the inclusive future of libraries, edited by Brian Wentz, Paul T. Jaeger, and John Carlo Bertot, focuses on the issues at the intersection of disability, accessibility, inclusion and libraries. The chapters in this volume provide best practices and innovative ideas to share amongst libraries, explore the roles that internet and communication technologies play in the context of inclusive libraries, illuminate the important contributions of libraries in promoting social inclusion of and social justice for people with disabilities, and help libraries to better articulate their contributions in these areas as they engage with disability groups, funders, policymakers, and other parts of their communities.
Improving services for patrons with print disabilities at public libraries : moving forward to become more inclusive / Jonathan Lazar, Irene Briggs -- Universally accessible makerspace recommendation to the District of Columbia public library / Rhett Moeller ... [et al.] -- Accessibility and the maker movement : a case study of the adaptive technology program at District of Columbia public library / Patrick Timony -- Creating a community-centered library for individuals with print disabilities : a blueprint and a challenge / Jill Lewis -- Developing accessible libraries and inclusive librarians in the 21st century: examples from practice / Ruth V. Small, William N. Myhill, Lydia Herring-Harrington -- A case study in practice : providing accessibility for persons with disabilities at the College of Staten Island library / Kerry Falloon -- Collection development, e-resources, and barrier-free access / Axel Schmetzke -- Supporting web accessibility with HTML5 and accessible rich internet applications : insights for libraries / Debra A. Riley-Huff -- Managing accessible library web content / Binky Lush -- The digital inclusiveness of state library websites / Norman E. Youngblood -- Digital inclusion, disability, and public libraries : a summary Australian perspective / Brendan Fitzgerald ... [et al.] -- Libraries and the future of equal access for people with disabilities : legal frameworks, human rights, and social justice / Paul T. Jaeger, Brian Wentz, John Carlo Bertot.
Print version record
Keywords: Language Arts & Disciplines -- Library & Information Science -- Administration & Management*.; Library & information services; Libraries and people with disabilities